100 Frailty Hot Clinics: Rapid Cga and Speciality Diagnostics Reduces Rates of Hospitalisation and Re-Attendance. (16th March 2021) - Lim, H J; Robson, R; Alexander, N; Cunningham, R; Encisa, D; Jhurry, R; Owusu, D; Remolan, A
Abstract: Introduction: Acute hospitalisation is associated with an increased risk of progressive frailty, morbidity and subsequent institutionalisation. North Middlesex University Hospital is an Acute District General Hospital with over 550 attendances to A&E per day. Comprehensive Geriatric Assessment (CGA) is the gold standard approach for a holistic multi-disciplinary assessment (MDT) of frail patients. A rapid access daily hot clinic service for frail patients opened using quality improvement (QI) methodology to deliver rapid CGA focusing on admission avoidance and early supported discharge. Method: 4 PDSA cycles were conducted. A process map identifying key moments in patient care was derived from time studies of the first 10 patients' journeys. Patients were triaged through the Geriatrician "hotphone" for acute admissions into the Hot Clinic. Dedicated clinic and waiting rooms were placed on the acute frailty unit (Amber) staffed by a dedicated Consultant Geriatrician and Health Care Support Worker working with the Frailty Ward Clerk, Frailty Specialist Nurse, Therapies, specialities in-reach and same-day diagnostics. A shared clerking proforma and subsequent CGA Discharge Summary were completed and emailed to the referrer the same day. Qualitative and Quantitative feedback was gained from referrers, patients and relatives through a structured questionnaire. Metrics were gathered including rate of admissions, re-attendance and use of enhanced community services. Results: From the first 48 Hot Clinic patients, there was a low 30-day re-attendance rate (17%—for unrelated reasons), low 30-day re-admission rates (4%) and low Did Not Attend rate (6%) for new referrals and high satisfaction scores for recommending the service (9-10/10) from patients, relatives and referrers. Conclusions: Early rapid MDT can reduce re-attendances and re-admissions to hospital in frail patients. A streamlined patient journey can be delivered by frailty-trained staff and in a suitable environment. QI Methodology enables a structured measurable approach to development of the Acute Frailty Pathway.